2020
DOI: 10.3390/cells9091999
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Multi-Layered Pancreatic Islets and Adipose-Derived Stem Cell Sheets Transplanted on Various Sites for Diabetes Treatment

Abstract: Islet cell transplantation is considered an ideal treatment for insulin-deficient diabetes, but implantation sites are limited and show low graft survival. Cell sheet technology and adipose-derived stem cells (ADSCs) can be useful tools for improving islet cell transplantation outcomes since both can increase implantation efficacy and graft survival. Herein, the optimal transplantation site in diabetic mice was investigated using islets and stem cell sheets. We constructed multi-layered cell sheets using rat/h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 35 publications
0
16
0
Order By: Relevance
“…In comparison to diabetic rats, AUC was significantly lower (p 0.002) in the treatment group with functioning graft, while it was significantly higher (p < 0.001) in comparison to values from normal rats. 2021)) and their ability to improve the islet function (Jung et al, 2011;Chen et al, 2013;Lee et al, 2020;Yamashita et al, 2021). One study demonstrated a better vascularization after ADSC implantation than with BM-MSCs in a myocardial infarction (MI) model (Paul et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In comparison to diabetic rats, AUC was significantly lower (p 0.002) in the treatment group with functioning graft, while it was significantly higher (p < 0.001) in comparison to values from normal rats. 2021)) and their ability to improve the islet function (Jung et al, 2011;Chen et al, 2013;Lee et al, 2020;Yamashita et al, 2021). One study demonstrated a better vascularization after ADSC implantation than with BM-MSCs in a myocardial infarction (MI) model (Paul et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated the angiogeneic potential of both ADSCs and BM-derived mesenchymal stem cells (BM-MSCs) (reviewed in ( Mazini et al, 2019 ; Liu and Holmes, 2021 )) and their ability to improve the islet function ( Jung et al, 2011 ; Chen et al, 2013 ; Lee et al, 2020 ; Yamashita et al, 2021 ). One study demonstrated a better vascularization after ADSC implantation than with BM-MSCs in a myocardial infarction (MI) model ( Paul et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The mouse islet sheet did not correct serum hyperglycemia in diabetic recipient mice in our study, although other researchers have reported that multi-layered cell sheets boost glycemic stability and insulin function[ 144 - 146 ]. Lee et al [ 147 ] constructed multilayered cell sheets using rat/human islets and human adipose tissue-derived stem cells. We have successfully generated islet sheets from Tg pigs with a pancreas-specific expression of green fluorescent protein ( PDX1-Venus Tg Pig) and transplanted them onto the liver surface (Figure 2 ).…”
Section: Application Of Pigs For the Development Of New Therapies Formentioning
confidence: 99%